JoJo the giant - Barclay, Jane, 1957- (Tundra Books ; Tundra Books of Northern New York, 2012)
Desperate to grow bigger even though his mother reassures him that good things come in small packages, little JoJo longs to run a race to win red Rocket Racer shoes but despairs at the thought of having to compete against large bullies.